Pengaruh Kompensasi Finansial dan Non-Finansial Terhadap Motivasi Kerja dan Kinerja Pegawai Pada Universitas Hasanuddin Di Makassar - Andi Jazai Aserina A. Mushawir; Mahlia Muis; Fauziah Umar (Hasanuddin Journal of Business Strategy, 2019)
This study aims to find out the effect of financial and non-financial compensation on work motivation and officials’ performance at Hasanuddin University, Makassar. This research was a qualitative approach. The populations were Education Officers of State Civil Apparatus of Hasanuddin University having a work period of more than 10 years. The data were obtained through observation, questionnaire, and documentation. Data processing and analysis were performed using SPSS (Statistical Product and Service Solution) version 23. The results of the research indicate that (1) there is a positive and significant financial and non-financial compensation on work motivation, (2) there is a positive and significant financial and non-financial compensation on officials’ performance, (3) there is a positive and significant financial and non-financial compensation on officials’ performance through work motivation.